Impact of routine completion angiography on outcome after carotid endarterectomy - Hoffmann-Wieker, Carola Marie; Harcos, Katharina; Ronellenfitsch, Ulrich; Demirel, Serdar; Böckler, Dittmar (Journal of vascular surgery, 2019)
Objective - The objective of this study was to analyze the impact of completion digital subtraction angiography (cDSA) after carotid endarterectomy (CEA) on technical and early clinical results. - Methods - This retrospective study included consecutive patients undergoing CEA from January 2011 to January 2015. Routine cDSA was performed in all patients. Study end points were the incidence of pathologic findings on completion angiography necessitating intraoperative revision, type of revision, periprocedural stroke rate, mortality, morbidity, and recurrent stenosis rate during follow-up (median, 5 months; range, 0-39 months). - Results - There were 827 procedures performed in 770 patients (male, 72.5%; median age, 70.6 years) with extracranial internal carotid artery (ICA) stenosis (asymptomatic, 57.3%); 426 patients underwent conventional endarterectomy (cCEA) with patch angioplasty (51.6%), 393 patients (47.5%) received an eversion technique (eCEA), and 8 patients (1%) underwent other revascularization. Immediate surgical revision based on angiographic findings after CEA was performed in 6.9% (57/827) of cases. Reasons for revision of the ICA were mural thrombus in 7.0% (4/57), dissections in 7.0% (4/57), residual stenosis in 8.7% (5/57), and intimal flaps of ICA in 1.8% (1/57). In six cases, combined pathologic changes of the ICA and external carotid artery led to revision. Thirty-five revisions (4.2%) were performed for isolated pathologic angiographic findings of the external carotid artery; in two cases, revision was performed for residual stenosis of the common carotid artery. There was no significant difference regarding the frequency of revision between surgical techniques (cCEA, 56.4%; eCEA, 63.6%; P = .76). However, mural thrombus as a reason for revision was more common in the cCEA group; plaque residues were more common in the eCEA group. Periprocedural (30-day) stroke rate was 0.5% (4/827); six additional patients suffered transient ischemic attack (0.7%). The mortality rate within 30 days was 0.1% (1/827); 30-day morbidity was 4.2% (35/827). The rate of recurrent stenosis (>50%) during follow-up was 0.8%. There was no significant correlation between pathologic findings on cDSA with consecutive revision and perioperative stroke rate, recurrent stenosis rate, mortality, or morbidity. - Conclusions - In this study, cDSA after CEA detected findings leading to immediate intraoperative surgical revision in a relevant proportion of cases. Therefore, cDSA represents a reasonable quality control without being associated with significantly prolonged operating times. Whether cDSA reduces perioperative stroke rate, procedure-related mortality, morbidity, or incidence of early recurrent stenosis cannot be proven with the current study design.